Parametric assessment of the technological and infrastructure state of food enterprises according to industry 4.0 technology development trends - Bagmet, Vadym (Management and Entrepreneurship: Trends of Development, 2023)
The purpose of this research is to present the developed parametric model for assessing the current technological and infrastructure state of food enterprises regarding the implementation of Industry 4.0. The research is performed using a method of linear combination of parameters with weights that reflect their relative importance in the final assessment. Methodology: In accordance with the chosen research topic, parameters were identified as the most crucial for forming future evaluation criteria to calculate the current technological and infrastructure state of a food enterprise regarding the implementation of Industry 4.0. This was achieved using the method of linear combination of parameters (Weighted arithmetic mean, The min-max scaling method) with weights that reflect their relative importance in the final assessment. The research finding is the ranges of assessing the current state of enterprises. Modern technologies and tools of Industry 4.0 are rapidly evolving both in the international and national markets. The digital transformation of business models opens up new opportunities and challenges for enterprises, encompassing the rational use of resources, socio-economic relationships, technological strategy, and the incorporation of the "Industry 4.0" concept into company activities. As a practical example for assessing the current state of technological and infrastructural support for enterprises in the food industry, the Ukrainian-Spanish Urozhay LLC  has been chosen. Based on the results of the conducted assessment, the current state of implementation and utilization of Industry 4.0 tools at the enterprise under consideration was determined. A set of recommendations and proposed measures aimed at improving the performance of the investigated enterprise has been provided, among which it is necessary to highlight: attracting additional investments, opening a new type of collective business involving small enterprises with different types of product portfolios. As a perspective for further research, the design of a unified production and trading hub is proposed, consisting of automated management systems, robotic stations, and physical and cloud data analytics systems. JEL Classification: F20, L59, O14